Price competition in the enlarged EU 27 export market and the role of foreign direct investment - Jens K. Perret (University of Wuppertal, Schumpeter School of Business and Economics, 2014)
From a microeconomic perspective competition between firms has been duely discussed. Extending microeconomic concepts to a macroeconomic level and considering competition between countries becomes more complex. The complexity issues is tackled in this study by extending a methodology developed in Borbely (2006) to account for specialization in specific sectors as well as price groups that under certain assumptions can be seen as a quality indicator. This study observes 27 EU countries - excluding Croatia - and Turkey. This allows for a view on the competition structure in the context of the EU common market.In a second step of the analysis it is analyzed whether FDI inflows impact the price - quality - level of a sector or the probability to switch to a higher or a lower price level in said sector. Where in other publications including borbely06 for selected EU countries a positive impact of FDI inflows is found, this study finds for the EU as a whole or the EU 15 or EU 10+1 (including Turkey) sub-groups no significant impact of FDI inflows on the price level or the probability to switch to another price level.
urn:nbn:de:hbz:468-20140813-092831-1
Keywords: 330